2016
DOI: 10.1186/s12933-016-0439-9
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of chemokine CC motif ligand 4 related mechanisms in diabetes mellitus and cardiovascular disease: friends or foes?

Abstract: Chemokines are critical components in pathology. The roles of chemokine CC motif ligand 4 (CCL4) and its receptor are associated with diabetes mellitus (DM) and atherosclerosis cardiovascular diseases. However, due to the complexity of these diseases, the specific effects of CCL4 remain unclear, although recent reports have suggested that multiple pathways are related to CCL4. In this review, we provide an overview of the role and potential mechanisms of CCL4 and one of its major receptors, fifth CC chemokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 120 publications
2
75
0
Order By: Relevance
“…Chemokines play essential roles in local in ammation, by attracting immune cells to the site of injury or in ammation (28)(29)(30). Previous studies have reported CCL2 levels to be independent predictors of cardiovascular events (29,30), and coherently we found CCL2 to be increased in participants with CAN.…”
Section: Chemotactic Cytokines Are Not Associated With Cardiovascularsupporting
confidence: 84%
“…Chemokines play essential roles in local in ammation, by attracting immune cells to the site of injury or in ammation (28)(29)(30). Previous studies have reported CCL2 levels to be independent predictors of cardiovascular events (29,30), and coherently we found CCL2 to be increased in participants with CAN.…”
Section: Chemotactic Cytokines Are Not Associated With Cardiovascularsupporting
confidence: 84%
“…As our group and others have reported, it is not common to find trans-protein quantitative trait loci (pQTLs) with large effect sizes and most trans-pQTLs occur in genes which encode receptors or that have other regulatory influences on the protein studied (46)(47)(48)(49)(50)(51). Thus, we hypothesize that one or more genes within the MS4A locus may be key modulators of sTREM2.…”
Section: Discussionmentioning
confidence: 78%
“…For example, variants located on 3p21.31 were significantly associated (rs145617407: β = 0.348, P = 2.58×10 -10 ) with plasma levels of macrophage inflammatory protein 1beta (MIP1b), a protein which is encoded by C-C motif chemokine ligand 4 (CCL4) located on 17q12 (50,54). The 3p21.31 locus contains genes which encode five members of the C-C motif chemokine receptor family (CCR1, CCR2, CCR3, CCR5, and CCR9) including a known receptor for CCL4 (CCR5) (55). Thus, we hypothesize that one or more genes within the MS4A locus are key regulators of sTREM2.…”
Section: Discussionmentioning
confidence: 99%